(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The best methods for human resource management in small-scale enterprises are examined in this research. The formality of human resource management procedures, such as the frequency of performance reviews and the possibility of on-the-job training, are correlated with the size of the company. A human resources policy still needs to be in place for the majority of small industry units